2017
DOI: 10.1186/s12943-017-0627-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of G protein-coupled receptor GPR87 promotes pancreatic cancer aggressiveness and activates NF-κB signaling pathway

Abstract: BackgroundPancreatic cancer is a highly lethal disease and has the worst prognosis of any major malignancy. G protein-coupled receptor GPR87 is reported to be overexpressed in multiple cancers. The clinical significance and biological role of GPR87 in pancreatic cancer, however, remain to be established.MethodsGPR87 expression in pancreatic cancer cell lines, paired patient tissues were determined using western blotting and Real-time PCR. Ninety-six human pancreatic cancer tissue samples were analyzed by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 35 publications
(41 reference statements)
1
66
0
Order By: Relevance
“…GPCRs also have excellent specificity relative to other endogenous molecules (in this case ACh relative to choline), whereas PBPs often must be tuned by protein engineering (our scaffold protein initially had tighter affinity for choline than ACh). However, GPCRs can be difficult to overexpress, can cause problems when they are 21,22 , and are more difficult to target to organelles than soluble PBPs. Furthermore, GPCRs and other receptors contain many specific localization/export/retention/binding sequences (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCRs also have excellent specificity relative to other endogenous molecules (in this case ACh relative to choline), whereas PBPs often must be tuned by protein engineering (our scaffold protein initially had tighter affinity for choline than ACh). However, GPCRs can be difficult to overexpress, can cause problems when they are 21,22 , and are more difficult to target to organelles than soluble PBPs. Furthermore, GPCRs and other receptors contain many specific localization/export/retention/binding sequences (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sensor responds (positively or negatively) to all molecules that normally bind the M3 receptor, precluding the use of GACh2.0 in combination with many cholinergic drugs. Finally, over-expression of GPCRs perturbs the function of endogenous proteins such as G-proteins 21,22 and can disrupt cellular behavior 23 , creating concerns that GACh2.0-expressing cells may have altered ACh and/or other signaling pathways.…”
mentioning
confidence: 99%
“…Previous studies have shown that the NF-κB signaling pathway not only plays a pivotal role in immune and inflammatory responses, but is also essential for tumorigenesis [14,15]. Specific targeting of the NF-κB signaling pathway has been intensively explored for its potential as a treatment for a variety of malignancies [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant regulation or mutations of GPRs, G proteins and downstream siganllings are implicated with various diseases such as heart failure [3], asthma [4] and bipolar disorder [5]. In addition, increasing evidences have pointed to GPRs and their downstream signallings as relevant players in cancer initiation and progression [6][7][8]. GPRs have been proved to play multiple roles in cell differentiation, cell proliferation, immune responses, invasion, angiogenesis and metastasis [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing evidences have pointed to GPRs and their downstream signallings as relevant players in cancer initiation and progression [6][7][8]. GPRs have been proved to play multiple roles in cell differentiation, cell proliferation, immune responses, invasion, angiogenesis and metastasis [7,9,10]. Thus, drugs targeted to GPRs for cancer prevention and treatment become promising.…”
Section: Introductionmentioning
confidence: 99%